Comparison of the efficacy and safety of intracervical dinoprostone gel and intravaginal misoprostol tablet as a cervical ripening agent - Shobha Mukherjee; Sujoy Mukherjee (Universiti Kebangsaan Malaysia, 2015)
Background: Cervical ripening is an important prerequisite for successful induction of labor, a procedure that is frequently necessary because of medical or obstetrical complications. Of several methods of ripening, intracervical dinoprostone gel and intravaginal misoprostol tablet are the most frequently used methods. Aims and Objectives: To compare the efficacy and safety of intracervical dinoprostone gel and intravaginal misoprostol tablet as a cervical ripening agent. Materials and Methods: A total of 138 pregnant women satisfying the inclusion criteria were studied. They were divided into two groups: 72 in group 1 (dinoprostone gel) and 66 in group 2 (misoprostol tablet). The safety and efficacy of both the drugs were analyzed. The primary outcome variables were change in Bishop’s score, induction to delivery (I-D) time, Apgar score, and incidence of abnormal uterine action. The secondary outcome variables were need for oxytocin, indication for caesarean section, and mode of delivery. Statistical analysis was done using the unpaired t-test and w2-test. Results: No difference was observed between the two groups with respect to change in Bishop’s score (3.015 vs 3.625, p 4 0.05), but I-D time was more for group 1 (i.e., 15.04 vs 11.48 h, p o 0.05). Apgar scores were also similar in both the groups, that is, the number of babies with Apgar score of o8 at 5 min was 3 for group 1 vs 6 for group 2, p 4 0.05. Abnormal uterine action was not seen at all in group 1, whereas three patients had this problem in group 2. In secondary variables, requirement of oxytocin was more in group 1 (i.e., 48 vs 22, p o 0.05). In various indications of caesarean section, none got operated for abnormal uterine action in group 1, whereas three patients got operated for this reason in group 2. Mode of delivery was similar in both the groups. Conclusions: Dinoprostone and misoprostol are similar in their action on cervical ripening. Misoprostol has an added benefit of being a uterotonic agent. Therefore, it has less I-D time. Low-dose of misoprostol has decreased the incidence of side effects.